Direct Observations of Precursor Short-Range Order Clusters of Solute Atoms in a LPSO-Forming Mg-Zn-Gd Ternary Alloy - Egusa, D.; Kawaguchi, K.; Abe, E. (Frontiers in Materials, 2019)
We have investigated short-range order (SRO) clusters of solute atoms in a Mg97Zn1Gd2 alloy which forms a long-period stacking/order (LPSO) phase, based on aberration-corrected scanning transmission electron microscopy (STEM) observations and first-principles calculations. High-angle annular dark-field (HAADF) STEM provides directly the individual Gd atom positions through significant atomic-number dependent Z-contrast, and their averaged image-processing have immediately shown up the representative SRO-Gd configurations being in favor of the second-nearest networks in the hcp-Mg structure. Interestingly, Zn atoms seem to be essentially placed at the particular sites within the SRO-Gd configurations to form D019-like ZnGd3 clusters, a validity of which are verified by STEM image simulations and first-principles calculations. These D019-like ZnGd3 clusters in the hcp-Mg matrix are likely to be a precursor sub-structure to the L12-type Zn6Gd8 clusters that are embedded in the local fcc layers in the LPSO structure. In fact, we find that these D019-like ZnGd3 clusters seem to form a layered atmosphere prior to the LPSO formation, providing an important clue on how the LPSO phases nucleate and grow.